PENGARUH KOMBINASI PAKAN ALAMI DAN BUATAN TERHADAP KELULUSHIDUPAN DAN PERTUMBUHAN LARVA IKAN SELAIS (Kryptopterus lais) - Agusnimar Agusnimar; Rosyadi Rosyadi (DINAMIKA PERTANIAN, 2013)
Study on the effect of the combination of natural and artificial foods on the survival and growth rate of selais (Kryptopterus lais) was done. The objective of the study was to know the effect of the several feed combination on the growth and survival rate of Kryptopterus lais. A completely randomized design was applied with five treatments and two replications. The combination of the treatments consisted of 5 levels i.e. (A): Giving Moina sp on the 2-13th day, followed by Tubifex sp on the 11-21st day and 30% Tubifex sp + 15% pellet on the 21-30th day; (B): giving Moina sp on the 2-13th day, followed by Tubifex sp on 11- 21st day and 30% Tubifex sp + 15% pellets on the 21-30th; (C ): giving Artemia sp on the 2-9th day, followed by Tubifex sp on 7-21st day and 30% on Tubifex sp + 15% pellets; (D): Giving Artemia salina on the 2-13th day, followed by Tubifex sp on the 11-21st day and 30% Tubifex sp + 15% pellet on the 21-30th day; (E): Giving Tubifex sp on the 2-13th day, followed by Tubifex sp on the 11-21st day and 30%, and Tubifex sp+15% pellets on the 21-30th day. The hhighest survival of larva was recorded at the treatement E (combination among Tubifex sp giving on the 1-13th day, Tubifex sp on the 11th day, 30% Tubifex sp + 15% pellet) namely 34.67%. While the highest growth of weight and length was found at the treatment D (giving Artemia salina on the 2-13th day, followed by Tubifex sp on the 11-21st day and 30% Tubifex sp+15% pellets on the 21-30th day), respectively, were 2.55 gr and 7.31 cm.